Increased maternal microchimerism after open fetal surgery - Saadai, Payam (Landes Bioscience, 2012)
Maternal-fetal cellular trafficking (MFCT) during pregnancy leads to the presence of maternal cells in the fetus and of fetal cells in the mother. Since this process may be altered in cases of pregnancy complications, we asked whether open fetal surgery leads to changes in microchimerism levels. We analyzed maternal and fetal microchimerism in fetuses who underwent open fetal surgery for repair of spina bifida and compared their levels to patients who had postnatal repair and to healthy controls. We found that maternal microchimerism levels were increased in patients who had open fetal surgery compared with controls. In contrast, patients who had fetal intervention at the time of delivery did not demonstrate increased microchimerism. These results suggest that open fetal surgery may alter trafficking. Given the importance of MFCT in maternal-fetal tolerance, we discuss potential implications for the field of preterm labor and transplantation tolerance.